الدراسة الميكانيكية الكوانتية (Ab initio) لمماكبات حلقي البروبيل فورم ألدهيد في الطور الغازي (Latakia University Journal -Basic Sciences Series, 2018)
تم التحقق من أن حلقي البروبيل فورم ألدهيد يتمتع بمماكبين فراغيين؛ إذ يتمتع المماكب cis بطاقة أخفض من طاقة المماكب trans، باستخدام طرائق الـ Ab initio عالية الدقة. تمت عملية البحث عن التمثيل الهندسي المتوازن، وحساب التواترات الاهتزازية بوساطة النظريات ذات السويات الحسابية DTF/6-311G(d,p)، وRHF/6-311G(d,p)، وRHF/6-31(d). سجلت الطاقات النسبية، والتواترات الاهتزازية التوافقية، والشدات النسبية للعصابات الاهتزازية تحت الحمراء، وكذلك الخصائص الترموديناميكية للمماكبين المتوازنين  cis) و (trans. تم تحديد سطوح الطاقة الكامنة للدوران الداخلي حول الرابطة C – C المركزية باستخدام الطرائق MP2/6-311G(d,p)، وRHF/6-311G(d,p)، وRHF/6-31(d). استنادا إلى هذه الدراسة، حسبت فروقات الطاقة بين المماكبين، والحواجز الكمونية للدوران الداخلي. تقدم النظرية ذات السوية     DFT/6-311G(d,p) انسجاما جيدا بين النتائج النظرية والقيم التجريبية المتوافرة لتفسير السلوك التماكبي للجزيئات. Two conformers of cyclopropyl formaldehyde have been investigated, where the cis isomers have lower energy than trans isomer, using high levels ab initio methods. Geometry optimizations and vibrational frequencies calculations have been performed by way of DTF/6-311G(d,p), RHF/6-311G(d,p), RHF/6-31(d)-level theories. Relative energies, harmonic vibrational frequencies, infrared intensities and thermodynamics properties of two conformers (cis and trans) are reported. Moreover, potential energy surfaces of internal rotation around C – C central bond of ground state of cyclopropyl formaldehyde were explored by way of HF/6-31(d), HF/6-311G(d,p) and MP2/6-311G(d,p) levels. Based on this study, the differences in energy between two conformers and the internal rotation barrier have been calculated. The significant agreement between the theoretical results and the available experimental values support the reliability of the DFT/6-311G(d,p)-level theory for describing the conformational behavior of molecules.